SISTEM PENJADWALAN PENGGUNAAN RUANGAN PERKULIAHAN MENGGUNAKAN VISUAL BASIC DAN MIKROKONTROLER - Irfan Dwiguna Sumitra (Paradigma, 2011)
Lecture room scheduling system design intended to address the problems of the use of the lecture room using a computer and some of the information posted on any lecture room. Computers installed Visual Basic 6.0 program serves as a database and perform ongoing scheduling simultaneously send information to every device information that is in every room lecture schedule the use of the lecture room. The device consists of a microcontroller AT89S51 information, LCD (Liquid Crystal Display) 4x20 and Buzzer. AT89S51 microcontroller serves as a processor of information that will be displayed on the LCD and activate the buzzer. 4x20 LCD serves as a viewer to information received by the microcontroller from the computer. Buzzer serves as an alarm to remind you that the time course lecturer will end soon. Scheduling system is able to provide information on any room lectures through information sent by the computer to the device information is displayed on the LCD so that faculty and students can see the ongoing lectures in a lecture room. Thus, the scheduling system is expected to overcome the limitations of the lecture room and the use of space beyond the time so it does not happen again delays both at the beginning and end of the course. Key word : Buzzer,  Computer, LCD 4x20, Microcontroller AT89S51, Visual Basic 6.0